Radiosynthesis and in vivo imaging of [11C]BTFP, a potent inhibitor of VEGFR2 - Ramesh Neelamegam; Thomas Chaly; J.S. Dileep Kumar (Results in Chemistry, 2022)
Altered expression of VEGFR2 is reported in the pathology of neurological, neuropsychiatric, brain malignancies and developmental disorders. PET imaging that allows for in vivo visualization of specific targets on the molecular level allows early detection, diagnosis and treatment monitoring non-invasively and accelerates therapeutic development. Our ongoing effort to derive a PET tracer that can be used to quantify the changes in VEGFR2 and resulted in the identification of N-(benzo furan-5-yl)-N-2,6-trimethylfuro[2,3–d]pyrimidin-4-amine (BTFP) (IC50 = 5.8 nM). In this report, the automated radiochemical synthesis and in vivo evaluation of a high affinity VEGFR2 ligand, [11C]BTFP by using PET is described. [11C]BTFP is synthesized in 35 ± 5% radiochemical yield by radiomethylating the N-desmethyl-BTFP precursor using [11C]CH3I. MicroPET studies in mice indicated a blood–brain barrier penetration of [11C]BTFP, with modest uptake and specific binding. Although, the low brain uptake of [11C]BTFP diminished its utility for in vivo imaging application, it can be used as a lead molecule for developing new PET tracers for central nervous system imaging.